Covid longa: fadiga, alterações do sono e Burnout em trabalhadores da saúde - Oliveira, Ítala de Brito (2023)
Long COVID syndrome is a debilitating disease that affects a large number of people, and the number of cases continues to increase. Initially, symptoms were denied, resulting in significant harm to affected individuals. Today, it is known that there is a variety of manifestations related to various organs and systems that need to be better established and understood. Knowledge about the late symptoms of COVID-19 syndrome can contribute to the addressing of specific therapies. The objective of this study was to identify changes such as fatigue, sleep disturbances, and burnout syndrome, in the period of 6-8 months after exposure to COVID-19, in healthcare workers. The study evaluated the long-term changes of a population of professionals served in the Unified Health System, from five hospitals, in the city of Fortaleza-Brazil, during the first epidemic of the disease, in 2020. The sample consisted of 199 professionals of both sexes, aged ≥18 years. Among a total of 700 individuals, 199 professionals, corresponding to approximately 20% of the population, were evaluated. The group included doctors, nurses, physiotherapists, psychologists, nutritionists, housekeepers, nursing technicians, occupational therapists, and general service professionals. The evaluated individuals were asked to respond about symptoms related to fatigue, sleep disturbances, and burnout manifestations. In this study, participants answered a virtual structured questionnaire for obtaining clinical-demographic information. Specific behavioral questionnaires and scales evaluating fatigue (Fatigue Severity Scale), daytime sleepiness (Epworth Sleepiness Scale), insomnia (Insomnia Severity Index), and Burnout syndrome (Burn-out questionnaire) were also applied. Fatigue was identified in 64.7% of individuals; moderate insomnia in 45.7%, and excessive daytime sleepiness in 46.2%. The insomnia (ISI), sleepiness (ESS), and Fatigue (FSS) indexes correlated with each other (r=0.46, p<0.005). The results showed that healthcare professionals who directly worked with COVID-19 patients after 6 months presented more fatigue, sleep disturbances, and Burnout syndrome. It was also observed that regardless of professional category, those with previous COVID-19 infection had more long COVID symptoms. In conclusion, healthcare professionals in direct contact with patients were more affected by residual or long COVID symptoms. Also, regardless of professional category, previous infection with the virus determined a higher frequency of symptoms of the referred syndrome.